ASPEK YURIDIS “AGREEMEENT TO MEDIATE” DALAM PENYELESAIAN SENGKETA PERBANKAN MELALUI MEDIASI - Tutik Nurul Jannah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2012)
Agreement to mediate is an agreement between the customer and the Bank in a banking mediation. Mediation is a process of settlement of dispute involving a mediator to assist the parties in dispute to achieve a settlement in the form of voluntary agreement to some or all of the problems disputed. According to Bank Indonesia Regulation No. 8/5/PBI/2006 as changed by PBI No. 10/1/PBI/2008 about Banking Mediation and SE BI No. 8/14/DPNP, June 1, 2006 about Banking Mediation, settlement can be done through banking mediation if the dispute between the customer and the Bank is caused by the non-fulfillment of the customer's financial claims by the Bank in settlement of the customer's complaint. The function of the banking mediation performed by Bank Indonesia is limited to the effort to assist the customer and the Bank to review the dispute basically in the framework of obtaining an agreement between the customer and the Bank. Bank Indonesia does not make a decision and or recommendation for the settlement of the dispute between the customer and the Bank.